2012
DOI: 10.5941/myco.2012.40.4.258
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression of Phanerochaete chrysoporium Glyoxal Oxidase and its Application for the Coupled Reaction with Manganese Peroxidase to Decolorize Malachite Green

Abstract: cDNA of the glx1 gene encoding glyoxal oxidase (GLX) from Phanerochaete chrysosporium was isolated and expressed in Pichia pastoris. The recombinant GLX (rGLX) produces H2O2 over 7.0 nmol/min/mL using methyl glyoxal as a substrate. Use of rGLX as a generator of H2O2 improved the coupled reaction with recombinant manganese peroxidase resulting in decolorization of malachite green up to 150 µM within 90 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
(29 reference statements)
0
5
2
Order By: Relevance
“…The optimum pH obtained under the tested conditions for both Pci GLOX enzymes was 6, which is in agreement with that previously reported for Ph GLOX ( 26 , 27 ). However, our results differ from those obtained by Son et al ( 25 ), who showed that the optimum pH for the recombinant Ph GLOX was 5. In our study, it was noticed that the enzymes were very sensitive to minor pH changes and they were less active at pH 5, which is a change of only 1 pH unit from the optimal pH.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The optimum pH obtained under the tested conditions for both Pci GLOX enzymes was 6, which is in agreement with that previously reported for Ph GLOX ( 26 , 27 ). However, our results differ from those obtained by Son et al ( 25 ), who showed that the optimum pH for the recombinant Ph GLOX was 5. In our study, it was noticed that the enzymes were very sensitive to minor pH changes and they were less active at pH 5, which is a change of only 1 pH unit from the optimal pH.…”
Section: Discussioncontrasting
confidence: 99%
“…The two purified glycosylated proteins were similar in size to Ph GLOX (68 kDa), which was also found to be N-glycosylated, with glycosylation accounting for about 16% of the total protein mass ( 12 , 23 ). Contrary to the optimum temperature for Ph GLOX, which is 30°C ( 25 ), the optimum temperature for both Pci GLOX described here was 50°C, and activity was still detected at 75 to 80°C. The two Pci GLOX enzymes were found to be similarly affected by temperature and were relatively stable at 50°C after 4 h of incubation.…”
Section: Discussioncontrasting
confidence: 90%
“…The maximum activity of MtGLOx was observed at pH 6.0 and 50 • C ( Figure 3A,B). These optimum conditions for MtGLOx were practically the same as described for the two glyoxal oxidases from P. cinnabarinus [27], but distinct from the P. chrysosporium enzyme (30 • C and pH 5.0) [38]. The residual activity after incubation at various temperatures was assayed at pH 6.0 using methylglyoxal as a substrate.…”
Section: Catalytic Properties Of Mtgloxmentioning
confidence: 92%
“…Moreover, some GLOxes are linked to the cell Wall Stress-responsive Component (WSC) domain that is predicted to be a cell-wall and membrane protein in yeast and fungi associated with cell wall integrity and stress responses [36,37]. Only three catalytic domains of GLOx enzymes from Phanaerochaete chrysosporium, Ustilago maydis, and Pycnoporus cinnabarinus fungi have been studied biochemically to date [26,27,34,38], but none were associated with such WSC domains. In the present study, we report the structural and functional characterization of a multidomain glyoxal oxidase from the thermo tolerant Myceliophthora thermophila M77 and show that 5-hydroxymethylfurfural as a new described substrate for this enzyme, demonstrating its potential in green enzymatic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…All these Primers were used to amplify cDNA and these were : 1. F: 5'-GCGAATTCATGTTGTCGCTGCTAGCCGTAGT-3 'R: 3'-CGTACGTACTCCAGGGTCGGCGGAGGGT-5' (Son et al, 2012).…”
Section: Pcr Primersmentioning
confidence: 99%